Bank Credit and Agricultural Sector Growth in Nigeria, 1990-2014: A Vector Error Correction Mechanism (VECM) Investigation. - Ikeora , Jackson J. E.; Andabai , Priye W.; Nneka B. , Charles-Anyaogu (African Journal of Education,Science and Technology (AJEST), 2017)
c